Gerakan Masyarakat Cinta Sehat (Germacis) sebagai Strategi Mengendalikan Penyakit Tidak Menular di Kampung Jogokariyan Yogyakarta - Trisnowati, Heni; Marlinawati, V. Utari; R.S, Naomi Nisari (Universitas Respati Yogyakarta, 2019)
Non-communicable diseases (NCD) have dominated the cause of death in Yogyakarta. Kampung Jogokaryan is a part of Yogyakarta City which has high cases of hypertension and diabetes mellitus. NCD is triggered by unhealthy lifestyles such as smoking habits, lack of physical activity and consume of less fiber foods. On the other hand, this village has a good social capital such as mutual cooperation habits, posyandu for the elderly, regular meeting groups of mothers and fathers. Based on these opportunities, Germacis has been conducted to control NCD and smoking habits in Kampong Jogokaryan, Yogyakarta.Keywords: healthy love community movement (Germacis), non-communicable diseases, control